Evolution in language studies - Marlyna Maros; Shanthini Pillai; Saadiyah Darus; Noorizah Mohd Noor (Penerbit Universiti Kebangsaan Malaysia, 2016)
The evolution of language research and practive is an ongoing endeavour. It is becoming more challenging with the advent of the digital age where the borders between the physical and the virtual are seamless and fluid. Throughout the years, research enquiries have emerged from within the traditional topical perspectives of various aspects of language studies to spectrums of interdisciplinary outlook. This book presents some of these enquiries that range from online language learning, classroom-based learning, linguistics in language learning, and literary studies. The topics covering explorations of online communication, classroom practices, translation, gender, linguistics, sociopragmatics, sociolinguistics, new literary genres, as well as expatriate writing reveal critical and creative engagements in the discipline and suggest potential avenues for future research. It is hoped that Evolution in Language Studies will inspire and stimulate the attention and interest of the academic community both and globally.